2018
DOI: 10.1016/j.atherosclerosis.2018.05.043
|View full text |Cite
|
Sign up to set email alerts
|

Ferritin, metabolic syndrome and its components: A systematic review and meta-analysis

Abstract: High triglycerides and glucose are the components more strongly associated with ferritin. Hepatic injury and BMI appear to influence the ferritin-MetS association, and a threshold effect of high ferritin concentration on the ferritin-high triglycerides association was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 52 publications
3
31
1
Order By: Relevance
“…Our findings are consistent with previous observation, in which the researchers showed that serum concentration of ferritin is connected with insulin resistance in PCOS women (38). Other studies also reported an association between serum ferritin levels and components of insulin resistance (18,22). Additionally, an elevated level of serum ferritin, especially in more insulin-resistant subjects, has been shown (6).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are consistent with previous observation, in which the researchers showed that serum concentration of ferritin is connected with insulin resistance in PCOS women (38). Other studies also reported an association between serum ferritin levels and components of insulin resistance (18,22). Additionally, an elevated level of serum ferritin, especially in more insulin-resistant subjects, has been shown (6).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, elevated serum ferritin levels have been observed in PCOS women (14)(15)(16). In a recent meta-analysis, it has been shown that serum ferritin concentration is connected with fasting plasma glucose, serum insulin concentration (17), and plasma triglycerides (TG) level (18). Additionally, studies revealed that serum ferritin levels are connected with homeostasis model assessment of insulin resistance (HOMA-IR) in a non-diabetic population but not in patients with impaired glucose tolerance (19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, there were more CVD risk factors with more plasma ferritin. Furthermore, it has been proven that, of all the MetS components, triglycerides and hyperglycemia are the variables that correlate the most with high plasma ferritin levels [ 37 ]. C reactive protein (CRP) is a protein of the pentraxin family, synthesized and released by endothelial cells in atherosclerotic plaques, hepatocytes, lymphocytes and macrophages, mainly in response to the increase of interleukin 7 (IL 7).…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, SF level was positively correlated with total cholesterol, TG, FBG, HOMA-IR, and hs-CRP after adjusting for age and BMI, but the association of MetS did not reach the level of significance after adjustment for BMI. A meta-analysis (Suarez-Ortegon et al, 2018) also found that the meta-regression for ferritin-MetS association identified weaker associations when the studies adjusted for BMI, but the role of adjustment for BMI in evaluating confounding factors should be considered. FAMHES (Tang et al, 2015) has not yet found an association between SF and (Kell & Pretorius, 2018).…”
Section: Discussionmentioning
confidence: 99%